The Effect of the Addition of Sugar Liquid on the Development of Bees (Apis mellifera) in a Regular Box - Mubarrok, Muhammad Tirta; Adriani, Adriani; Yurleni, Yurleni; Kuswandi, Wawan (Jurnal Peternakan, 2025)
ABSTRACT. Sugar liquid can be used as supplementary feed for honeybees (Apis mellifera) because it may influence population development, egg production, and larvae, thereby enhancing colony productivity. This study aimed to determine the effect of adding sugar liquid on the development of Apis mellifera populations in standard hives. The research utilized 12 standard hives of Apis mellifera, each containing seven frames, with sugar liquid applied in four different treatments and three replicates. The treatments involved sugar liquid at a ratio of 3:1 (3 parts sugar and 1 part water), with levels of P0 = 0 kg, P1 = 0.33 kg/week, P2 = 0.66 kg/week, and P3 = 1 kg/week. The study employed a randomized block design (RBD), and data were analyzed using variance (ANOVA). Significant differences between treatments were further tested using Duncan's test. The results indicated that the addition of sugar liquid as supplementary feed did not significantly affect (P>0.05) the population, egg number, or larvae count of Apis mellifera. The study concludes that adding up to 1 kg of sugar liquid per week meets the basic nutritional needs of Apis mellifera but is not sufficiently effective in significantly increasing population, egg, or larval numbers.